Implementation of the Right to Education for Abandoned Children in Salatiga City - Saragih, Jogi Talar; Rumahorbo, Erika Magdalena; Siahaan, Herbin Marulak (Jurnal Indonesia Sosial Sains, 2024)
This study was conducted to examine the implementation of the right to education for abandoned children in the city of Salatiga. The main objectives are, first, to explain how Salatiga city government regulations play a role in fulfilling the right to education for abandoned children, and second, to explore how these regulations are implemented. Using a normative legal research method, which employs both statute and conceptual approaches, the study draws on secondary legal materials from literature, legal journals, expert opinions, and official websites. The findings reveal that in Salatiga, the right to education for abandoned children is implemented through both formal and non-formal education. Formal education focuses on basic education, while non-formal education includes vocational training and entrepreneurial coaching. The results of this research show that the application of formal and non-formal education by the Salatiga city government has successfully increased access to education for abandoned children. This study contributes significantly to promoting more inclusive and sustainable educational policies for abandoned children, with recommendations for improved regulations and more targeted vocational education programs.